2018
DOI: 10.1021/acs.nanolett.8b03042
|View full text |Cite
|
Sign up to set email alerts
|

In-Place Modulation of Rectification in Tunneling Junctions Comprising Self-Assembled Monolayers

Abstract: This paper describes tunneling junctions comprising self-assembled monolayers that can be converted between resistor and diode functionality in-place. The rectification ratio is affected by the hydration of densely packed carboxylic acid groups at the interface between the top-contact and the monolayer. We studied this process by treatment with water and a water scavenger using three different top-contacts, eutectic Ga–In (EGaIn), conducting-probe atomic force microscopy (CP-AFM), and reduced graphene oxide (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 44 publications
3
58
1
Order By: Relevance
“…[ 1 ] Molecular tunneling junctions, in which the charge transport properties of molecules are exploited in devices, have considerable potential in this context because subtle changes at the atomic scale can translate into unique and useful effects at the device level. [ 2,3 ] By exploiting the chemical nature of molecular electronics, these effects are exemplified in photoisomerization, [ 4–8 ] , protonation, [ 9,10 ] electrostatic gating, [ 11,12 ] reduction–oxidation, [ 13 ] etc., giving rise to molecular resistors and molecular diodes in both single‐molecule junctions and large‐area junctions comprising self‐assembled monolayers (SAMs). The majority of studies on effects that rely on external inputs, such as conductance switching, are observed ex situ, i.e., new junctions are formed and characterized instead of molecules being switched in‐place, be they single‐molecule break‐junctions in which molecules are repeatedly trapped and released [ 14 ] or large‐area junctions formed by raising and lowering a tip on top of a SAM.…”
Section: Figurementioning
confidence: 99%
“…[ 1 ] Molecular tunneling junctions, in which the charge transport properties of molecules are exploited in devices, have considerable potential in this context because subtle changes at the atomic scale can translate into unique and useful effects at the device level. [ 2,3 ] By exploiting the chemical nature of molecular electronics, these effects are exemplified in photoisomerization, [ 4–8 ] , protonation, [ 9,10 ] electrostatic gating, [ 11,12 ] reduction–oxidation, [ 13 ] etc., giving rise to molecular resistors and molecular diodes in both single‐molecule junctions and large‐area junctions comprising self‐assembled monolayers (SAMs). The majority of studies on effects that rely on external inputs, such as conductance switching, are observed ex situ, i.e., new junctions are formed and characterized instead of molecules being switched in‐place, be they single‐molecule break‐junctions in which molecules are repeatedly trapped and released [ 14 ] or large‐area junctions formed by raising and lowering a tip on top of a SAM.…”
Section: Figurementioning
confidence: 99%
“…The observation that a depends on the identity of the moiety in contact with the top electrode can be understood by the tunneling-hopping mechanism shown in In operando rectification modulation While it is important to verify the mechanism of rectification in GESAMs, the ability of fullerenes and ferrocenes to effect rectification is not new; however, combined with the unique properties of GESAMs, these molecules can be used to modulate rectification while a junction is being observed under bias. This in operando control over the properties of a tunneling junction is a technological step forward from in situ and in-place modulation 8 and, unlike conductance-switching, 7 is unique to molecular-electronic devices. To allow for exchange in assembled Au TS /PTEG-1//PTEG-1//EGaIn junctions, we formed them by contacting the GESAMs of PTEG-1 with conical EGaIn tips in a microfluidic channel with precise control over back pressure (see Experimental section for details), as shown in Fig.…”
Section: Characterization Of Bilayers and Monolayersmentioning
confidence: 99%
“…1 Molecular electronics, which studies the charge transport properties of molecules and their applications in devices that realize their properties, has extraordinary potential in this context because subtle changes at the atomic scale can translate into unique and useful effects at the device level. 2 By exploiting the chemical nature of molecular electronics, these effects are exemplified in photoisomerization, [3][4][5][6][7] protonation, 8,9 electrostatic gating, 10,11 reduction-oxidation, 12 etc., giving rise to molecular resistors and molecular diodes in both single-molecule junctions and large-area junctions comprising self-assembled monolayers (SAMs). However, effects that rely on external inputs, such as conductance-switching, are rarely observed in situ; i.e., new junctions are formed and characterized instead of the original ones, be they single-molecules in break-junctions or raising and lowering a tip of eutectic Ga-In (EGaIn) on top of a SAM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar influence of the protonation on the LUMO position was reported for SAMs, in which the protonation of the terminal carboxylic acid groups converts back and force the molecular junctions between a resistor and a rectifying diode. 33 Protonation has also been used in combination, with light irradiation to block the spiropyran molecule in its merocyanine isomer and avoiding its spontaneous back switching to the spiropyran form. 34 Finally, protonation has been used to induce destructive-quantum-interference in diketopyrrolopyrrole derivative, leading to a reversible decrease of the conductance (1 order of magnitude) upon protonation.…”
Section: Introductionmentioning
confidence: 99%